PENINGKATKAN KOMPETENSI GURU DALAM MEMBUAT RPP MELALUI PELATIHAN KKG SEKOLAH DI SD NEGERI DANAWARIH 03 KECAMATAN BALAPULANG KABUPATEN TEGAL SEMESTER I TAHUN PELAJARAN 2018/2019 - Nur Khikmawati (Dwija Inspira: Jurnal Pendidikan Multi Perspektif, 2020)
The formulation of the problem of this research is (1) Can the school KKG training activities improve the ability of teachers to prepare lesson plans for teachers of SD Negeri Danawarih 03 for the 2018/2019 academic year? (2) How big is the increase in teacher competence in preparing RPP after participating in the KKG School training at SD Negeri Danawarih 03 for the 2018/2019 academic year? (3) Can the school KKG training activities change teacher behavior in compiling RPP at SD Negeri Danawarih 03 for the 2018/2019 academic year? This school action research was conducted for 6 months. The subjects of this study were 7 teachers of SD Negeri Danawarih 03. This study was designed with 2 cycles and each cycle consisting of 4 stages, namely planning, acting, observing, and reflecting. The results showed that the ability to make mathematics teaching aids from cycle I to cycle II had a significant increase. The final result obtained from this study is that 100% of 7 SDN Danawarih 03 teachers have achieved the very good category in making lesson plans in accordance with process standards. Suggestions relating to this research, among others, are for teachers to have to master and understand how to make lesson plans that are in accordance with the rules, according to instructions, be creative and innovative so that learning is more interesting so that it has an impact on student achievement.